Increased Serum Klotho With Age-Related Aortic Stiffness and Peripheral Vascular Resistance in Young and Middle-Aged Swine - Guo, Xiaomei; Kassab, Ghassan S. (Frontiers in Physiology, 2020)
The anti-aging function of Klotho gene has been implicated in age-related diseases. The physiological importance of Klotho in the progression of arterial stiffness with aging, however, remains unclear. The goal of this study is to determine the correlation of circulating Klotho with early age-related aortic stiffening and peripheral hemodynamics. We measured serum Klotho levels in a group of pigs with age ranges of 1.5-9 years and investigated the relationship between Klotho levels and biomarkers of aortic stiffening with aging, including aortic pulse wave velocity (PWV), augmentation index (AIx) and pulse pressure (PP). The effects of aortic stiffening on peripheral vascular resistance, compliance and function were also evaluated. We found that increased aortic stiffness occurred at middle age (>5 years old), as evidenced by an increase in PWV and AIx (P<0.001), but with no changes in blood pressure and PP. With advancing age, increased femoral vascular resistance positively correlated with aortic PWV and AIx (P<0.01). No significant difference in endothelium function and arterial compliance for femoral and small peripheral arteries was observed between young and middle-aged groups. The serum Klotho levels were lower in young and higher in middle-aged pigs (P<0.001), and a positive correlation was found between Klotho and aortic PWV, AIx, and femoral vascular resistance (P<0.01). Our findings suggest that early-aged aortic stiffening has adverse effect on peripheral hemodynamics, independent of blood pressure levels. Elevated Klotho secretion was associated with increased aortic stiffness and peripheral vascular resistance with aging.